2001
DOI: 10.2337/diabetes.50.9.2105
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Palmitic Acid Induce Degeneration of Myofibrils and Modulate Apoptosis in Rat Adult Cardiomyocytes

Abstract: Several studies support the concept of a diabetic cardiomyopathy in the absence of discernible coronary artery disease, although its mechanism remains poorly understood. We investigated the role of glucose and palmitic acid on cardiomyocyte apoptosis and on the organization of the contractile apparatus. Exposure of adult rat cardiomyocytes for 18 h to palmitic acid (0.25 and 0.5 mmol/l) resulted in a significant increase of apoptotic cells, whereas increasing glucose concentration to 33.3 mmol/l for up to 8 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 38 publications
4
110
1
1
Order By: Relevance
“…In the heart, when supply of fatty acid exceeds tissue oxidative capacity, the accumulation of lipids decreases cardiolipin synthesis [36] and induces myofibrillar degeneration [10], leading to lipotoxicity and apoptosis. Given that exogenous C 2 -ceramide mimics the deleterious effects of fatty acid, and that inhibition of ceramide formation blocks these toxic effects caused by high fat, several studies have suggested that de novo ceramide formation plays an important contributory role in apoptosis [8,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the heart, when supply of fatty acid exceeds tissue oxidative capacity, the accumulation of lipids decreases cardiolipin synthesis [36] and induces myofibrillar degeneration [10], leading to lipotoxicity and apoptosis. Given that exogenous C 2 -ceramide mimics the deleterious effects of fatty acid, and that inhibition of ceramide formation blocks these toxic effects caused by high fat, several studies have suggested that de novo ceramide formation plays an important contributory role in apoptosis [8,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, an increase in intracardiac fatty acid concentration can overwhelm fatty acid oxidation. In this situation, fatty acids accumulate and can, either by themselves, or via their channelling towards the production of second messengers like ceramide, provoke apoptosis [9,10]. Enlargement of the intracardiac fatty acid pool during diabetes may similarly overpower the tissue capacity for utilisation, resulting in an accumulation of cardiotoxic lipid, which may be implicated in cardiac myocyte apoptosis [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…5 . Fatty acids were dissolved at 10 mmol/l in culture medium containing 11% fatty acid-free BSA (Sigma) under N 2 -atmosphere, shaken overnight at 37°C, sonicated 15 min, and sterile-filtrated (stock solution) (15,26). For control experiments, BSA in the absence of fatty acids was prepared, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, long-term exposure to saturated fatty acids such as palmitate appear highly toxic, whereas monounsaturated fatty acids such as oleate protect against both palmitate-and glucose-induced ␤-cell apoptosis (18,31). It is of interest to note that similar toxic effects are also observed in non-␤-cells such as cardiac cells (32). Lipoproteins may affect ␤-cell survival in a similar way, whereby VLDL and LDL are pro-apoptotic and HDL is protective (33,34).…”
Section: Dyslipidemia Leptin and Inflammation: Linking Obesity To ␤mentioning
confidence: 99%